THE MISOGYNY OF DORIAN GRAY: A FEMINIST CRITICAL DISCOURSE ANALYSIS OF WOMEN REPRESENTATION IN OSCAR WILDE’S WRITING (Contemporary Journal of Social Science Review, 2025)
Oscar Wilde’s The Picture of Dorian Gray, despite being legally and morally questioned at the time of its publishing, has endured the passage of time to establish itself as one of the canonical classics of English literature. To this day, The Picture of Dorian Gray entertains a wide readership from all over the world. However, Wilde’s portrayal of female characters still remains highly problematic. This paper addresses misogyny in The Picture of Dorian Gray and focuses on Wilde’s stereotypical and oppressive ideological treatment of the female characters. It employs Michelle Lazaar’s Feminist Critical Discourse praxis in order to analyze whose interest Wilde portrays throughout the novel and to what extent do the female characters get to have their own voice. The analysis reveals that Wilde stereotypically categorizes women and strips them of their agency. The male characters describe most of the female experience in the book and therefore, none of the information about any woman in The Picture of Dorian Gray comes from a reliable source. Moreover, Wilde manipulates Sybil Vane’s character to portray a highly unrealistic, exoticized woman through a girl of barely seventeen. The research uncovers how with the survival of great classics the misogyny of these books continues to survive into the present as well.